Gambaran Intensitas Bermain Game Online pada Mahasiswa S1 Keperawatan Tingkat Akhir di Universitas Harapan Bangsa - Restu Fathur Roby'ad; Ema Wahyu Ningrum; Roro Lintang Suryani (Universitas Harapan Bangsa, 2021)
At this time, technology is developing very rapidly and never stops development, one of which is online games. Playing online games can be done by all walks of life from children to adults and the elderly. The purpose of this research to find out the picture of the intensity of playing online games on undergraduate nursing students final level at the nation's hope university. The type of research used is descriptive survey by questionnaire using content validity test. Sampling using total sampling which includes inclusion and exclusion criteria. Respondents in this study were 44 undergraduate nursing students. The data was taken using a game playing intensity questionnaire on line. The results of this study showed 36 (81.8%) respondents played online games 4 hours in a day, 25 (56.8%) respondents play online games 2-3 days in one weeks, 26 (59.1%) respondents stated that they did not have full attention when playing online games, 31 (70.5%) respondents expressed a neutral feeling after playing games.